The cell [videorecording (DVD)] - Lopez, Jennifer, 1970-; Vaughn, Vince; D'Onofrio, Vincent (New Line platinum series., 2000)
Using an experimental technique, a therapist enters the mind of a serial killer to save a child's life. Her experience becomes a nightmare when she cannot find her way out.